Household indoor concentration levels of NO2, SO2 and O3 in Nsukka, Nigeria. (1st January 2021) - Agbo, Kevin Emeka; Walgraeve, Christophe; Eze, John Ikechukwu; Ugwoke, Paulinus Ekene; Ukoha, Pius Oziri; Van Langenhove, Herman
Abstract: The concentrations of nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ) and ozone (O3 ) were determined at 20 locations (10 urban and 10 rural) in both indoor (cooking areas) and ambient air in the Nsukka area during two one-week sampling periods in both dry (11–January 26, 2019) and wet (11–August 22, 2017) seasons. During the dry season, the pollutants were also measured in the living rooms (urban and rural locations) and bedrooms (urban locations). Radiello passive samplers were used to sample the target pollutants. The indoor concentration in the kitchens ranges from 15 to 722 μg/m³ (median: 174, IQR:74–336 μg/m³) for NO2, 3–101 μg/m³ (median: 5, IQR:4–9 μg/m³) for SO2 and 2–46 μg/m³ (median: 10, IQR:5–15 μg/m³) for ozone. Within the urban household, the median concentrations of the NO2 (94, IQR: 64–175 μg/m³) in the kitchens were larger than in other rooms by at least a factor 2, in contrast to SO2 (3–4 μg/m³) and O3 (14–20 μg/m³) median levels which were respectively similar in all the rooms. The indoor to outdoor (I/O) ratio with respect to the kitchens varied from 2 to 435 for NO2 and 0.6 to 25 for SO2 . The O3 levels could be a factor 8, 18 and 25 higher outdoors than found respectively in the kitchens, living rooms and the bedrooms. The concentrations of NO2 are higher in households using solid fuels such as firewood (101–722 μg/m³; n = 11) and charcoal (134–356 μg/m³; n = 2) compared to those using LPG (19–174 μg/m³; n = 4). Seasonal variation of the concentration levels was observed for both indoor and outdoor environments, the outdoor concentrations of NO2, (median: 22 μg/m³, range: 10–72 μg/m 3 ), and O3 (median: 64 μg/m³, range:14–106 μg/m 3 ) in dry season were significantly (p ≤ 0.001) larger than the corresponding levels (median: 4 μg/m³ range:1–28 μg/m³) and (median: 10 μg/m³, range: 8–13 μg/m 3 ) respectively in wet season. The concentration levels of outdoor SO2 (median: 4 μg/m³, range: 3–5 μg/m 3 ) median: 4 μg/m³, range: 3–4 μg/m³ were similar in both seasons. The dry season indoor SO2 (median: 9 μg/m³, range:3–101 μg/m 3 ) and O3 (median: 15 μg/m³, range: 10–46 μg/m 3 ) are larger than the corresponding (median: 5 μg/m³, range: 4–8 μg/m 3 ) and (median: 5 μg/m³, range: 2–15 μg/m 3 ) wet season levels. However, the concentration of indoor NO2 (median 174 μg/m³, range: 18–480 μg/m³) in the dry season was lower than found (median 207 μg/m³, range: 15–722 μg/m³) in wet seasons. This work provides some novel data indicating poor indoor air quality in the study area. Highlights: Most (87%) households in Nsukka rely on standby power generators. Half the households use kerosene-in-lantern for lighting and solid fuel for cooking. The median indoor NO2 is a factor 4 larger in firewood compared to LPG-kitchens. Rural kitchen NO2 and SO2 are ≥4 times larger compared to urban kitchen in dry season. The ambient NO2 and O3 in dry season are a factor 6 larger compared to in wet season.